Jaringan Alumni dan Reproduksi Tradisi Kitab Kuning: Studi Peran Strategis Organisasi Alumni KESAN ( Keluarga Santri Langitan) Widang Tuban dalam Mempertahankan Otentisitas Keilmuan Pesantren. - Fahrudi, Emi (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
This study examines the strategic role of alumni networks in reproducing the tradition of the kitab kuning and preserving pesantren scholarly authenticity, based on a case study of the KESAN (Keluarga Santri Langitan) Alumni Organization in Widang, Tuban. Using a qualitative approach and case study methods (in-depth interviews, observation, and secondary data analysis), the findings show that KESAN acts as a Reproducer of Habitus (Bourdieu) through disciplined kitab kuning instruction and as a Guardian of Tradition by filtering modernization through regular musyawarah.The study identifies four main mechanisms: maintaining an intellectual alumni network for authentic knowledge transmission; reproducing santri habitus through discipline and modesty; transmitting cultural capital (knowledge of kitab kuning, Arabic proficiency, and religious authority) to the community; and supporting pesantren economic development through alumni entrepreneurship. The findings show that alumni organizations can adapt modern technologies without eroding tradition while reinforcing resistance to globalization. This study affirms Bourdieu’s cultural reproduction theory in the pesantren context, highlighting alumni as cultural agents linking tradition with contemporary dynamics. The sustainability of pesantren scholarly authenticity depends on strong alumni networks and contextualized teaching adaptations.